A bottom-up appraisal of the technically installable capacity of biogas-based solid oxide fuel cells for self power generation in wastewater treatment plants. (1st February 2021) - Sechi, Sonja; Giarola, Sara; Lanzini, Andrea; Gandiglio, Marta; Santarelli, Massimo; Oluleye, Gbemi; Hawkes, Adam
Abstract: This paper proposes a bottom-up method to estimate the technical capacity of solid oxide fuel cells to be installed in wastewater treatment plants and valorise the biogas obtained from the sludge through an efficient conversion into electricity and heat. The methodology uses stochastic optimisation on 200 biogas profile scenarios generated from industrial data and envisages a Pareto approach for an a posteriori assessment of the optimal number of generation unit for the most representative plant configuration sizes. The method ensures that the dominant role of biogas fluctuation is included in the market potential and guarantees that the utilization factor of the modules remains higher than 70% to justify the investment costs. Results show that the market potential for solid oxide fuel cells across Europe would lead up to 1, 300 MW of installed electric capacity in the niche market of wastewater treatment and could initiate a capital and fixed costs reduction which could make the technology comparable with alternative combined heat and power solutions. Highlights: We integrate solid-oxide fuel cells (SOFCs) in wastewater treatment (WWT). SOFCs are efficient co-generation devices but hindered by high capital costs. Technical SOFC potential in Europe WWT, up to 1370 MW, may promote cost reduction.